Pengaruh Metode Pembelajaran Diskusi, Perhatian Orang Tua dan Motivasi Belajar Terhadap Hasil Belajar IPS Siswa SDN Gugus Bumi Nikel Bohodopi Morowali - Ismawati Musa; Sudiyono; Yuli Ifana Sari (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
Motivation to learn can function as a driving force in achieving achievement. The approach used in this research is a quantitative approach. Researchers chose the type of experimental research. The purpose of this study was to determine the effect of the discussion learning method, parental attention and learning motivation on social studies learning outcomes of SDN Gugus Bumi Nickel Bohodopi Morowali Elementary School. The results of the analysis are 1). the results of the t test and reinforced by the results of the ANOVA test found that partially the use of the discussion method had an effect on student social studies learning outcomes. 2). the results of the t test and reinforced by the results of the Anava test found that partially parental attention influences student social studies learning outcomes. 3). the results of the t test and reinforced by the results of the Anava test found that partially student learning motivation influences student social studies learning outcomes. 4). ANOVA test shows that the use of the discussion method, student learning motivation, and parental attention influence student social studies learning outcomes together. The conclusion is that discussion learning methods, parental attention and learning motivation affect social studies learning outcomes of SDN Gugus Bumi Nickel Bohodopi Morowali students.